UNIVERSIDADE FEDERAL DO RIO GRANDE: REVISING POLITICAL-INSTITUCIONAL MOVEMENTS - Vera Isabel Caberlon (Editora da Universidade de Santa Cruz do Sul, 2009)
As analytic cutting on the path of three decades of Universidade Federal do Rio Grande, aspects of organization and related subjects to the teaching and the research are discussed. In that perspective, it is made documental revision of minutes and resolutive documents produced by the University Council, maximum organ of deliberation of the institution, in the decades of 1970, 1980 e 1990. To the analysis of those documents, understood as the institutional political vehicles, comments are increased on events happened in the first decade of the century XXI, enlarging understanding possibilities about the manifestation of different rationalities that are present in the way of being of the university. Key-words: Universidade Federal do Rio Grande. Teaching. Research. Organization modalitites. Rationalities.